The Relationship Between Attitude And Higher Order Thinking Skills (Hots) Among Secondary School Students - et. al., Mohd Saifulkhair Omar , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study would be to determine the attitude of students in secondary schools towards science and the degree of Higher Order Thinking Skills (HOTS). The objective of the research is also to examine the connection between the dimensions of the student's attitude and HOTS. This study is a quantitative method which is a correlation study. The questionnaire was used for the collection of respondent’s information. The questionnaire was divided into two sections, which are: (A) Students' attitude towards science and (B) Higher Order Thinking Skills (HOTS). The attitude toward science using an instrument was adapted and modified by Harery (2007) from the Science Attitudes Inventory which was developed by Lilia et al. (2003). The HOTS survey was consequently designed by the researchers centered on the 2001 Bloom's Taxonomy and based on the questions adapted and updated from Pentaksiran Tingkatan 3 (PT3) 2016 and 2017. A total of 89 secondary school students were randomly selected from the two secondary schools in Kuala Nerus, Terengganu. The study found that student’s attitude towards science was moderate (mean = 3.08), while HOTS level was low (mean = 1.28). However, there was a substantial connection between the dimensions of the science importance in society of the student attitude variables and the dimensions of evaluating and creating HOTS variables. Therefore, The Ministry of Education Malaysia (MOE) must plan the programs and activities to increase the awareness and understanding of the students about the importance of science in society.